Effect of widowhood on the risk of disability among the elderly in China - Pang, Jiahui; Xu, Shouyi; Wu, Yuanyang (Frontiers in Psychiatry, 2023)
Deteriorating health status of widowed elderly becomes an important restriction factor affecting the realization of healthy aging in China. This paper explored the effect of widowhood on the disability risk of the elderly in China and its disparities in different groups, and further investigated influencing channels and moderating effects. It was found that, widowhood significantly increases the risk of disability, and the result is still robust after changing survey samples. The risk of disability is aggravated among people who were males, lived in urban areas, were educated and 60~70year-old. The effect is mainly from psychological stress and unhealthy behavior. Meanwhile, increasing financial support and contact frequency from children, and increasing social activities are beneficial to reduce the negative effect. The above conclusions suggested that, there is an urgent need for children's support within family, social support from society and long-term care system to cope with deteriorating health of widowed groups.